Efektivitas Pengembangan Kompetensi Profesionalisme Guru Madrasah Tsanawiyah Negeri 1 Ternate - Gani, Rusna (Sekolah Tinggi Agama Islam Babussalam Sula, 2021)
Constitution 1945 clearly stated that each nation has right for education access and quality of education, as will result to the quality of human resources. Good quality of education will be produced by good quality teacher or professional teacher in their job. The result of teacher competent test 2015 shows the average number of teachers still under the standard of government. However, the province of Maluku Utara on the position of 33 per 34 in professionality and teaching technique. It is important to do the teaching competency improvement. Madrasah Tsanawiyah Negeri 1 Ternate has been done various professional teaching competency improvement. The study aims to examine the effectiveness of professional teaching competency improvement at Madrasah Tsanawiyah Negeri 1 Ternate. In answering the research question, descriptive qualitative technique was used with the support of primary and secondary data. Data collection was carried out at Madrasah Tsanawiyah Negeri 1 Ternate by means of observation, interviews, and surveys (questionnaires) of 36 teachers. The results show professional teaching competency improvement program have been carried out by the school and the local government, but the internal factors of teachers become obstacles so that competency development is still less effective.